Ricin as a Biothreat Agent: From Molecular Mechanisms to Clinical Toxicology, Forensic Aspects, and Risk Mitigation. - Pohanka, Miroslav; Gurumallesh Prabu, Poorani (BioMed Research International, 2026)
Ricin, a potent ribosome‐inactivating protein derived from the seeds of Ricinus communis L., represents a significant threat in the context of biological warfare and terrorism due to its high toxicity, ease of extraction, and lack of a specific antidote. This review provides a comprehensive examination of ricin's biochemical structure, toxicological mechanisms, and clinical manifestations, alongside its historical and potential use as a weapon. The paper explores the global distribution and utility of the castor bean plant, outlines the molecular basis of ricin's cytotoxicity, and evaluates current medical and technological countermeasures. Furthermore, it assesses international legal frameworks and policy instruments aimed at mitigating the misuse of biological agents. Case studies of ricin‐related incidents underscore the toxin's appeal to both state and nonstate actors, highlighting the need for enhanced surveillance, public awareness, and interdisciplinary preparedness. The findings emphasize the dual‐use dilemma posed by ricin and advocate for sustained international cooperation to address emerging biothreats.